PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2020-2023 - Purwatiningsih, Eka; Rahman, Arif (Jurnal Ekonomi Sakti, 2024)
Manufacturing industry companies have an important role as the pillar of the country's economy and at the same time the main driver to get out of the economic downturn amid the hampering of the Covid-19 container. Sales of inventory is one of the strategies used by companies to increase profits. This study was conducted to determine the effect of cash turnover, inventory turnover and accounts receivable turnover on profitability (ROA) in food and beverage industry companies listed on the IDX in 2020-2023 which is the focus of this study. The method used in this research is descriptive exploratory with a quantitative approach. The data used in this study are secondary data obtained from the official website of the Indonesia Stock Exchange using purposive sampling techniques for research samples. There were 13 companies as samples that presented complete financial reports in accordance with predetermined criteria, and the years used were four years. Multiple linear regression analysis was used in this study for data analysis. The hypothesis tests used are partial hypothesis tests (t tests), simultaneous hypothesis tests (f tests) and coefficient of determination tests using SPSS 27. The test results in this study show that cash turnover, accounts receivable turnover and inventory turnover have no simultaneous effect on profitability. Keywords: Cash Turnover, Receivables Turnover, Inventory Turnover and Profitability